Factors Affecting Early Marriage in Central Java Province - Urip Tri Wijayanti (Randwick International of Social Science Journal, 2020)
BKKBN provides an ideal age for marriage, namely 20 years for women and 25 years for men. These ways are steps to avoid divorce, domestic violence and early marriage. The reality is that the cases of early marriage still happen. One of them is in the province of Central Java. The purpose of this study is to analyze the description of perpetrators’ early marriage and the factors affecting it. This research uses the quantitative method with cross sectional study design, using IDHS raw data for 2017. The results showed that most perpetrators of early marriage at the age of 45-49 years 276 people (22.9%), first married at the age of 15-19 years 1104 (91.8 %), living in rural areas 723 people (60.1%), low education only graduated from elementary school 503 people (41.8%), covered 764 people (63.5%) with jobs as sales 251 people (32.9%) and wealth index on the index lower middle 333 people (27.7%). The affecting factor early marriage is education level. While the factors of residence, wealth index and employment status do not affect. BKKBN recommendation and the ministry of education coordinate with each other in promoting twelve-year compulsory education, through socialization by Family Planning Counseling or always call as PKB and through popular media so that the whole community gets information about the importance of education so they don't get married early./ device has increased from 49.42% in 2017 to 56.25% in 2019.